Systematic synthesis of ZIF-67 derived Co3O4 and N-doped carbon composite for supercapacitors via successive oxidation and carbonization. (20th April 2021) - Chen, Tzu-Yang; Lin, Lu-Yin; Geng, Dong-Sheng; Lee, Pin-Yan
Abstract: Zeolitic imidazolate framework-67 (ZIF67) composed of cobalt metal and 2-methylimidazole is one of the attractive metal organic frameworks for energy storage, due to the possible formation of cobalt oxide and N-doped graphite via oxidation and carbonization processes. It is the first time to develop cobalt oxide and N-doped graphite in one ZIF67 derivative as active material for supercapacitor (SC), which stores charges via redox reactions and electric double-layered behaviors. Six active materials with careful designs are constructed, including carbonized ZIF67 (C67), oxidized C67 (C67/O), oxidized ZIF67-covered C67 (C67/O67), oxidized ZIF67 (O67), carbonized O67 (O67/C), and carbonized ZIF67-covered O67 (O67/C). Detailed formation process and mechanism of these active materials are provided. The highest areal capacitance (CA ) of 332.3 mF/cm 2 at 20 mV/s is obtained for C67/O electrode, due to the suitable composition of Co3 O4 and N-doped graphite as well as the particle-assembled polyhedron structure with high porosity. The asymmetric SC composed of C67/O electrodes shows a potential window of 1.0 V and the maximum energy density of 0.87 Wh/kg at power density of 150 W/kg. Excellent cycling stability with CA retention of 100% and Coulombic efficiency of 100% after 4000 times repeatedly charge/discharge process is also achieved for this asymmetric SC.